Sex differences in inflammatory parameters after shoulder arthroplasty and blood loss - Hertling, Stefan; Schleußner, Ekkehard; Loos, Franziska Maria; Eckhardt, Niklas; Kaiser, Mario; Graul, Isabel (Frontiers in Surgery, 2024)
BackgroundIn many diseases, sex differences in diagnostics and therapy play role that is increasingly becoming recognized as important. C-reactive protein (CRP) and white blood cell (WBC) levels are determined as inflammatory markers to detect inflammation and even infection after total shoulder arthroplasty (TSA). The general course of white blood cell, CRP, and hemoglobin (Hb) levels after TSA is well known, but there is insufficient evidence of a possible association with sex. Therefore, we aimed to investigate whether there is an influence of sex on CRP, WBCs, and Hb after TSA in the first 10 days after surgery in a complication-free course in male and female patients and to re-evaluate the specific postoperative CRP, WBC, and Hb course with their maximums (minimum for Hb) and further course until the end of the inpatient period.MethodsWe retrospectively studied patients treated with TSA, reverse shoulder arthroplasty (RSA), and prosthesis replacement between 2015 and 2021. Patients with active inflammation, rheumatoid arthritis, secondary osteoarthritis, active cancer, and documented postoperative complications were not included. CRP, WBC, and Hb levels before shoulder arthroplasty (SA) and up to 10 days after SA were recorded and analyzed for sex differences.ResultsData from a total of 316 patients (209 women and 107 men) were finally analyzed. There were no sex differences in the CRP and WBC values, but women had significantly lower preoperative Hb values, postoperative Hb values, and minimum Hb values. There were no significant differences in Hb, CRP, or WBC levels in the prosthesis exchange group.ConclusionThe progression of CRP and WBC levels showed no sex-specific significant differences after TSA within the first 7 postoperative days. The study confirmed a decreased Hb value for women at all stages of SA. Blood loss was significantly higher for RSA than for TSA for both men and women.